The role of telehealth in the fight against COVID-19 and the evolution of the Peruvian regulatory framework - Curioso, Walter H. (2020)
Information and communication technologies (ICT) in health play a fundamental role in the management of COVID-19. This pandemic has rediscovered telehealth and has accelerated the use of digital platforms with health-oriented services. Within the context of the COVID-19 pandemic, the Peruvian Government has issued several regulations aiming to promote its use. The objective of this paper is to discuss the role of telehealth, and the evolution of its regulatory framework in Peru. Likewise, the initiatives developed and implemented by the Peruvian College of Physicians (PCP) regarding ICT use for healthcare within the framework of COVID-19 are described, such as "Observatorio CMP" (PCP Observatory), and the technological platforms: “Alo CMP” (Hello PCP) and “Salud a un Clic” (Health in a Click). Finally, the paper analyzes some current challenges for ICT in healthcare during the COVID-19 pandemic